Large-scale model of the axisymmetric kinematic dynamo - Sraibman, Laura (2016)
A formulation of a kinematic dynamo is presented, based on a previously derived self-consistent procedure for obtaining large-scale models for complex system of equations. The model has only a small number of parametrized variables: the small-scale magnetic diffusivity, the scale of the large-scale fields, and a factor in the explicit expression of the αφφ component of the α tensor. Explicit expressions of what corresponds to the other components of the α tensor and of the diffusivity tensor are derived in terms of the large-scale meridional flow and of the differential rotation law, without introducing additional parameters. A very simple simulation of a solar-like dynamo, employing the model without meridional flow shows reasonable magnetic field evolution, with a cycle duration of about 2/3 that of the Sun, shift of the magnetic field from mid-latitudes towards the equator, poleward migration of the radial field at high latitudes, and correct phase relation between radial and azimuthal components.